MENAKAR KINERJA PERSEDIAAN BAHAN MELALUI TURN OVER RASIO (TOR) PADA UMKM PERTANIAN : Inventory Performance, Turn Over Ratio, UMKM - Burhan, Umar (GEMA EKONOMI, 2020)
Inventory for business units is a support for production activities, so that the inventory stock is neither too large nor too small, because it is directly related to the costs incurred. Likewise in the agricultural industry, there is a tendency for commodity prices to fluctuate and have high turnover. In order to increase inventory turnover at minimal cost, it requires careful inventory management. Inventory turnover is one indicator of an inventory's performance. Performance measurement can be done by calculating the material turnover ratio (TOR). The purpose of this study is to measure the performance of raw material inventory through the calculation of Turn Over Ratio (TOR). This research was conducted at one of the agricultural MSMEs in Gresik, which produces packaged rice. The data used are primary data from observation and documentation, in the form of stock data and the use of raw materials for six months, from January to d. June 2020. The results showed that the performance of raw material inventory in the warehouse was still low, with a TOR value of only 0.08 s / d. 3.05 times and the long duration of storing raw material inventories in warehouses ranges from 8.19 s / d. 322.60 days, during the six months of observation.